PENGARUH KONTEN TIKTOK @partaigerindra TERHADAP KEPUTUSAN MEMILIH BAGI PENGIKUT PADA PEMILU TAHUN 2024 - Trinaldi, Fikri; Yesicha, Chelsy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to examine the influence of the TikTok account @partaigerindra’s content on the voting decisions of its followers during the 2024 General Election in Indonesia. TikTok was chosen due to its widespread popularity among young voters and its potential as a political communication platform. The study employs a quantitative approach using a survey method. The sample consists of 100 respondents, all of whom are followers of the @partaigerindra TikTok account and eligible voters. The independent variable in this study is the quality of TikTok content, measured using the 7C communication criteria (clarity, concise, concrete, correct, coherent, complete, and courteous). The dependent variable is the voting decision. The theoretical framework is based on the Stimulus–Organism–Response (S-O-R) theory. Data were analyzed using simple linear regression with the assistance of SPSS version 25. The results indicate that the content of @partaigerindra's TikTok account has a positive and significant influence on voting decisions, with a coefficient of determination (R²) value of 0.472. This means that 47.2% of the variation in voting decisions can be explained by the quality of the TikTok content, while the remaining 52.8% is influenced by other factors not examined in this study. The significance value (p-value) of 0.000 < 0.05 confirms that the alternative hypothesis is accepted. Thus, it can be concluded that the better the quality of TikTok content presented by the @partaigerindra account, the greater its influence on the voting decisions of its followers. Keywords: TikTok, Social Media Content, Voting Decision